When was the Seminary of Nueva Caceres Founded? A Historiographical Excursus - Calacday, Jethro (Archīum Ateneo, 2019)
When was the Seminario Conciliar de Nueva Caceres (later known as the Holy Rosary Seminary) founded? Did it originate from a certain Casa de Clérigos allegedly in existence since the seventeenth century? Existing histories answer the second question in the affirmative. However, the claim that the Casa de Clérigos was continuous with the seminary is unfounded; this claim emerged only in the 1940s, but it has been widely accepted as historical truth. This essay asserts that Bishop Juan Antonio Gallego de Órbigo established the seminary on 11 May 1785, an entity distinct fromthe Casa.KEYWORDS: SEMINARIES • PHILIPPINE CATHOLIC CHURCH • BIKOL • MYTH MAKING • HISTORIOGRAPHY